If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -45 = 6x + 10 Reorder the terms: -45 + X = 6x + 10 Reorder the terms: -45 + X = 10 + 6x Solving -45 + X = 10 + 6x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + X = 10 + 45 + 6x Combine like terms: -45 + 45 = 0 0 + X = 10 + 45 + 6x X = 10 + 45 + 6x Combine like terms: 10 + 45 = 55 X = 55 + 6x Simplifying X = 55 + 6x
| 7-3[5t-10]=67 | | 5x+15=22x | | 3u+4=-177 | | 8y+2(y-9)=3(y+1)-2 | | X-6=x+13 | | 2[5-3v]+9v=28 | | 104=8/d | | 3(4+w)=2(1+w) | | 3x+181y=98 | | 3y-6+3x=9y | | 7x+23=5x-17 | | 64x-x^3=0 | | r-7.6=-7.3 | | 6[1-4w]=-18 | | 14-6y-12-y=-33 | | 5x-36+6=0 | | a/34=18 | | -4(x+1)=-5x | | -3x+5x-19=-19 | | 8y^6-27=0 | | 3x-6+3y=9x | | 7-8x-3x=62 | | 8x+(-21)=3 | | 90/100=14.4/x | | -11/2-5 | | X+6=12+2x | | X+18+x=-14 | | 9t-4+t=0 | | -8x-5y=9 | | x+6/5=x+8/7 | | 4=p/27 | | 9x=5x-36 |